Modeling of fatigue crack propagation of multiple site using deterministic and probabilistic method - Romlay, Fadhlur Rahman Mohd; Ariffin, Ahmad Kamal; Mohamed, Nik Abdullah Nik (Penerbit Universiti Sains Malaysia, 2004)
The new method to modeling fatigue crack propagation compare with the classical inference is stochastic method. One approach to stochastic modeling is to randomize the coefficients of an established determinictic model to represent material inhomogenity (Ditlevsen and Olsen,1986). A random process to generate a stochastic data by multyplying the deterministic dynamics of fatigue crack growth (Lin and Yang, 1985; Spencer et al., 1989).